Determinants of escape from echo chambers: The predictive power of political orientation, social media use, and demographics. Issue 2 (June 2023) - Chan, Chi Kit; Zhao, M M; Lee, Paul SN
This study aims to understand the determinants of escape from echo chambers. Social media users can control the content to which they are exposed by confining their contacts to like-minded individuals. The resulting echo chamber effect can reinforce existing views and discourage rational discussion. We conducted a survey with a representative sample of 1969 respondents in 2020. Contrary to common expectation, a liberal political orientation was insignificant in predicting reference to differing views, but political partisanship, media trust, time spent on social media, education levels, and gender were significant. Those who spent more time on social media and had lower trust in media were found to refer to other views more frequently and were less susceptible to the echo chamber effect. The results of this study suggest that open-mindedness, independence, critical scepticism, and social activeness are significant resources for one to escape from the echo chamber.